Teacher and Parent Training to Improve Education Quality in Remote Areas in MIS Al-Afkari - Rahmalia Kurnia Wardani (Rahis Cendekia Indonesia, 2024)
This study explores the impact of teacher and parent training on improving the quality of education in remote areas, focusing on MIS Al-Afkari as a case study. Using a qualitative descriptive method, data were collected through interviews, observations, and document analysis involving teachers, parents, and school administrators. The findings revealed that the training programs significantly enhanced teaching practices, increased parental involvement, and contributed to more positive student behavior and learning motivation. Teachers became more confident and adopted interactive teaching methods, while parents began to actively support their children’s learning at home. Although challenges such as time constraints and limited resources were encountered, the overall impact of the training was positive and transformative. The study concludes that empowering both educators and families is essential to improving educational outcomes in under-resourced and geographically isolated communities.